2002
DOI: 10.1126/science.1073338
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Efficient Platinum(0)-Carbene Complexes As Hydrosilylation Catalysts

Abstract: The hydrosilylation reaction enables the production of silicon polymers. Platinum-carbene complexes are reported that catalyze the hydrosilylation reaction of alkenes with remarkable efficiency and exquisite selectivity and avoid the formation of platinum colloids. By-products, typically encountered with previous catalytic systems, are suppressed with these platinum derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
229
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(241 citation statements)
references
References 11 publications
6
229
1
5
Order By: Relevance
“…[9] In a previous communication, we have reported that a novel class of platinum(0) carbene complexes 10 displayed good reactivity and excellent selectivity in the hydrosilylation of the model alkene, 1-octene. [10] In this article, we report the preparation of a variety of such platinum derivatives and the results of our study on the hydrosilylation of a range of functionalised alkenes catalysed by these organometallics. In addition, some insights into the mechanism of this transformation will be discussed.…”
mentioning
confidence: 99%
“…[9] In a previous communication, we have reported that a novel class of platinum(0) carbene complexes 10 displayed good reactivity and excellent selectivity in the hydrosilylation of the model alkene, 1-octene. [10] In this article, we report the preparation of a variety of such platinum derivatives and the results of our study on the hydrosilylation of a range of functionalised alkenes catalysed by these organometallics. In addition, some insights into the mechanism of this transformation will be discussed.…”
mentioning
confidence: 99%
“…The Pt(NHC)(dvtms) complexes have been reported to be effective catalysts for hydrosilylation. 31 In the current study, the introduction of NHCs generally led to an improvement in the turnover number (TON) values of the catalysts. For example, the IMes-ligated platinum complex 4a resulted in an 8-fold improvement in the TON to 40 (Entry 2), whereas the IPr complex 4b gave none of the desired borylated product (Entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously proposed that the dvtms ligand in the platinum precursor decomposed prior to the formation of the catalytically active platinum species in hydrosilylation reactions involving Pt(NHC)(dvtms). 31,41 With this in mind, we investigated the reaction of dvtms with 1a in the presence of Pt(ICy)(dvtms) 4g to examine the reactivity of dvtms under the catalytic conditions used in the current CH borylation reaction. APCI-MS analysis revealed that the dvtms was completely consumed under the reaction conditions to give the corresponding tetraborylated product (eq 6).…”
mentioning
confidence: 99%
“…Markós group recently reported an NHC-Pt complex system that successfully catalyzed alkene hydrosilylation reactions, and demonstrated superior selectivity and activity compared to the commercial Speiers and Karstedts catalysts. [23,24] The NHC-Pt catalyst showed remarkable efficiency and selectivity, and avoided the formation of platinum colloids. Encouraged by these reports, MPP-NHC/pyrrolidine-Pt catalyst D was developed to catalyze olefin hydrosilylation reactions (Scheme 2).…”
mentioning
confidence: 99%